PENGGUNAAN MULTIMEDIA INTERAKTIF BERBASIS VIDEO ANIMASI DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA KELAS V DI SEKOLAH DASAR - Abdali, Yusuf; Anwar, Herson; Nadjamuddin, Asriyati (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This research aims to examine and explore the use of interactive multimedia based on animated videos in mathematics subjects and what are the supporting and inhibiting factors for the use of interactive multimedia based on animated videos in learning in Class V of SD Muhammadiyah 4 Limboto. This research uses qualitative research with a descriptive approach. Data was collected through observation, interviews and documentation. The subjects of this research were the homeroom teacher as a mathematics teacher and class V students at SD Muhammadiyah 4 Limboto. The research results show that the use of interactive multimedia based on animated videos has a positive impact on improving mathematics learning. Students become more motivated and enthusiastic in participating in lessons. Apart from that, this media helps students understand abstract mathematical concepts more easily through attractive visualizations. Teachers also feel that this media is very helpful, because it can convey material more effectively and attract students’ attention. The use of interactive multimedia based on animated videos in mathematics learning at SD Muhammadiyah 4 Limboto shows an increase in students’ understanding of the material being taught, as well as increasing student participation and interaction during the learning process. This research suggests that the use of interactive multimedia based on animated videos continues to be developed and applied in learning, and integrated with other learning methods to achieve effective and optimal results.